Bespoke automated linkage to enable analysis of covid deaths by ethnicity. - Shelley Gammon; Rachel Shipsey; Charlie Tomlin; Josie Plachta (International Journal of Population Data Science, 2022)
In early 2020 there was intense media speculation that ethnicity and Covid-19 deaths were correlated. However, the existing method of adding ethnicity to death records resulted in low linkage rates for very recent deaths. We designed and implemented a bespoke linkage in three days enabling accurate reporting to the nation.